Myocarditis and diaphragmatic rhabdomyolysis with respiratory failure in a patient with metastatic melanoma treated with Nivolumab. (April 2022) - Baldessari, Cinzia; Pugliese, Giuseppe; Venturelli, Marta; Greco, Stefano; Ferrara, Leonardo; Longo, Giuseppe; Dominici, Massimo; Depenni, Roberta
Introduction: Immunotherapy dramatically changed history of melanoma patients with a clinical benefit never seen before. Nevertheless, severe and unexpected adverse effects can occur, fortunately rarely. Case presentation: We reported the case of a 75-year-old male patient affected by metastatic melanoma who developed myocarditis and acute rhabdomyolysis with secondary diaphragmatic dysfunction and consequent pulmonary restrictive syndrome after Nivolumab monotherapy. Blood tests and ultrasonography of the diaphragm revealing left hypokinesis suggested a Nivolumab-related rhabdomyolysis, as an immune-mediated adverse event. The rhabdomylolysis involved the diaphragm with consequent diaphragmatic weakness and respiratory distress. Mangement & outcome: The patient had a slow but slight and progressive improvement of symptoms and vital signs post-treatment with high-dose corticosteroids. Discussion: With this case report, we want to highlight the importance of rapid recognition and treatment of rare and unexpected, but potential serious immune-related adverse events. These events might happen despite the remarkable clinical benefits of immune checkpoint inhibitors. We do not know which patients will benefit from these therapies and why, when and in which cases adverse event will occur: we must not lower our attention.